Congestion management in restructured power systems for smart cities in India. (January 2018) - Guguloth, Ramesh; Kumar, T.K. Sunil
Highlights: The development of smart cities in India will require a smart grid for power generation, transmission and distribution systems with a continuous power supply. The power transmission line is one of the major elements to supply continuous power in the smart cities via smart grid. Transmission line congestion is a major technical problem, which results in market inefficiencies and instability. Congestion must be relieved in order to maintain the system is in a secure state. The coordinated FACTS device and MG based CM method are proposed to relieve congestion with the objective of minimizing system total production costs and increasing the reliability. The optimal placements of the FACTS device and MG are obtained by using real power flow (RPF) and transmission line relief (TLR) sensitivity indices. This high-performance transmission line support system creates a better smart grid system so that it is better equipped to supply uninterruptible power to smart cities from the grid. Abstract: The development of smart cities in India will require a smart grid for power generation, transmission and distribution systems with a continuous power supply. The transmission line is one of the major elements to supply continuous power to the smart cities via a smart grid. Transmission line congestion is a major technical problem, which must be relieved in order to maintain the system is in a secure state. The present work proposes a combined FACTS device and a microgrid based congestion management (CM) method for relieving transmission line congestion. The optimal placements of the FACTS device and microgrid are obtained by using real power flow (RPF) and transmission line relief (TLR) sensitivity indices. The proposed method has been demonstrated on an IEEE 14 bus test system. The FACTS and MG based CM approached when combined were found to be superior to the performance when the methods are carried out individually. Graphical abstract: Figure represents the optimal power flow (OPF) solution of an IEEE 14 bus test system with a TCSC at line-3 and a DG unit on load bus-14. The congestion management involving coordinating actions of TCSCs and DGs, which are placed simultaneously at their optimal location in the 14-bus test systems. In this figure, a DG 2 and a TCSC have been placed at their optimal locations (TCSC at line-3 and DG at load bus 14) to relieve congestion in line-2 (connecting the bus-1 to bus-5). As a first step, the 10 MW DG 2 is placed on load bus-14 as the best optimal location, and OPF solution is obtained, which shows that the congestion condition remains in line-2. As a second step, the TCSC is placed in line-3 at its best optimal location and the OPF solution for the system with both DG 2 and TCSC are obtained. From OPF solutions, as shown in Fig. 1, it is evident that the congestion condition is relieved in line-2, while the MVA limit is below 1.0 p.u. This work could be helpful in creating a smart grid by relieving congestions of the transmission line with the objective of ensuring uninterruptible power supply to developing smart cities in India.